Hotel Hyatt Regency - Rodríguez, León (1992)
El autor nos invita a descubrir, a través de su mirada, sus impresiones en el acercamiento a la obra.
Keywords: ALEMPARTE BARREDA & ASOCIADOS; HOTELES; CHILE; SANTIAGO DE CHILE; ALEMPARTE, SERGIO; BARREDA, ERNESTO; WEDELES MANUEL; BESANCON YVES; ALEMPARTE JOSÉ GABRIEL